Consensus Statement for the Prescription of Pain Medication at Discharge after Elective Adult Surgery. Issue 1 (1st January 2020) - Clarke, Hance A.; Manoo, Varuna; Pearsall, Emily A.; Goel, Akash; Feinberg, Adina; Weinrib, Aliza; Chiu, Jenny C.; Shah, Bansi; Ladak, Salima S. J.; Ward, Sarah; Srikandarajah, Sanjho; Brar, Savtaj S.; et al.
ABSTRACT: This Consensus Statement provides recommendations on the prescription of pain medication at discharge from hospital for opioid-naïve adult patients who undergo elective surgery. It encourages health care providers (surgeons, anesthesiologists, nurses/nurse practitioners, pain teams, pharmacists, allied health professionals, and trainees) to (1) use nonopioid therapies and reduce the prescription of opioids so that fewer opioid pills are available for diversion and (2) educate patients and their families/caregivers about pain management options after surgery to optimize quality of care for postoperative pain. These recommendations apply to opioid-naïve adult patients who undergo elective surgery. This consensus statement is intended for use by health care providers involved in the management and care of surgical patients. A modified Delphi process was used to reach consensus on the recommendations. First, the authors conducted a scoping review of the literature to determine current best practices and existing guidelines. From the available literature and expertise of the authors, a draft list of recommendations was created. Second, the authors asked key stakeholders to review and provide feedback on several drafts of the document and attend an in-person consensus meeting. The modified Delphi stakeholder group included surgeons, anesthesiologists, residents, fellows, nurses, pharmacists, and patients. After multiple iterations, the document was deemed complete. The recommendations are not graded because they are mostly based on consensus rather than evidence.